Combined Microautoradiography–16S rRNA Probe Technique for Determination of Radioisotope Uptake by Specific Microbial Cell Types In Situ - Ouverney, Cleber C. (American Society for Microbiology, 1999)
We propose a novel method for studying the function of specific microbial groups in situ. Since natural microbial communities are dynamic both in composition and in activities, we argue that the microbial “black box” should not be regarded as homogeneous. Our technique breaks down this black box with group-specific fluorescent 16S rRNA probes and simultaneously determines (3)H-substrate uptake by each of the subgroups present via microautoradiography (MAR). Total direct counting, fluorescent in situ hybridization, and MAR are combined on a single slide to determine (i) the percentages of different subgroups in a community, (ii) the percentage of total cells in a community that take up a radioactively labeled substance, and (iii) the distribution of uptake within each subgroup. The method was verified with pure cultures. In addition, in situ uptake by members of the α subdivision of the class Proteobacteria (α-Proteobacteria) and of the Cytophaga-Flavobacterium group obtained off the California coast and labeled with fluorescent oligonucleotide probes for these subgroups showed that not only do these organisms account for a large portion of the picoplankton community in the sample examined (∼60% of the universal probe-labeled cells and ∼50% of the total direct counts), but they also are significant in the uptake of dissolved amino acids in situ. Nearly 90% of the total cells and 80% of the cells belonging to the α-Proteobacteria and Cytophaga-Flavobacterium groups were detectable as active organisms in amino acid uptake tests. We suggest a name for our triple-labeling technique, substrate-tracking autoradiographic fluorescent in situ hybridization (STARFISH), which should aid in the “dissection” of microbial communities by type and function.